Perilaku Konsumtif Gamers Genshin Impact terhadap Pembelian Gacha - Cynthia Angelia; Fauzi Akbar Maulana Hutabarat; Ngajudin Nugroho; Arwin Arwin; Ivone Ivone (Journal of Business and Economics Research (JBE), 2021)
The purpose of this study is to empirically examine the effect of gamers' consumptive behavior on gacha purchases in the Genshin Impact Game. Gacha is a game based on the player's chance and luck. Most of these games are usually free-to-play games with a gacha system as an incentive to use real currency to collect rare (limited) items. The research method used is a quantitative type. The number of research samples is 250 people from the population of Genshin Impact players whose number is unknown, with the sampling technique is accidental sampling. The large influence of consumptive behavior on the purchase of gacha can be seen in the results of the coefficient of determination (R2) as a percentage of 74.5%. With the results of this coefficient, it can be concluded that the purchase of gacha by 74.5% is influenced by the consumptive behavior of the players, while the remaining 25.5% is contributed by other factors that can be explained by other variables outside the model